Homer-3 antibody in autoimmune cerebellar syndromes: a potentially treatable mimic of MSA-C – A review - Chunowski, Patryk; Madetko-Alster, Natalia; Alster, Piotr (Frontiers in Immunology, 2025)
Autoimmune cerebellar ataxia (ACA) associated with anti-Homer-3 antibodies is a rare but increasingly recognized immune-mediated neurological condition. It represents a potentially treatable cause of sporadic cerebellar syndrome and may clinically mimic primarily multiple system atrophy of the cerebellar type (MSA-C), and less frequently, other atypical parkinsonian disorders. Because of the significant clinical overlap with neurodegenerative diseases, particularly MSA-C, Homer-3–associated ACA may be underdiagnosed or misdiagnosed, delaying effective treatment. This narrative review synthesizes the currently available literature on anti-Homer-3 immunoglobulins, with a focus on their pathophysiological role, diagnostic utility, therapeutic response, and clinical differentiation from neurodegenerative conditions. Homer-3 is a postsynaptic scaffold protein expressed in Purkinje cells, where it plays a key role in calcium signaling through metabotropic glutamate receptor pathways. Antibodies against Homer-3 have been identified in patients with a wide range of neurological and neuropsychiatric symptoms, most commonly with subacute cerebellar ataxia. Neuroimaging in such cases frequently shows cerebellar atrophy or inflammation, and cerebrospinal fluid analysis often reveals inflammatory markers. The treatment with immunotherapy, particularly corticosteroids and intravenous immunoglobulins, which has showed encouraging results, however therapeutic outcomes can vary. The aim of this review is to collect and analyze all currently available data on anti-Homer-3–associated ACA, with the goal of raising clinical awareness and emphasizing the importance of early recognition and aggressive intervention.